Upaya menigkatkan kompetensi guru dalam menyusun rencana pelaksanaan pembelajaran melalui pemberdayaan kegiatan kelompok kerja - Aliasmi Aliasmi (SCHOULID: Indonesian Journal of School Counseling, 2019)
The phenomenon in the field illustrates that the existence of the working group or forum has not yet provided a significant contribution to the improvement of teacher competency. Various obstacles faced by teachers, principals, and supervisors currently in an effort to create active and effective activity groups. The purpose of this study is to describe efforts to improve teacher competency in developing learning implementation plans through empowering teacher working group activities. This type of research is the principal's action research. The data analysis technique was analyzed descriptively using the percentage formula. Based on the results of the study it was found that: 1) To improve competence in the learning process carried out through empowering competency activities in the learning process carried out through empowering teacher working group activities on a regular basis as much as 2 cycles, each cycle of 2 meetings, each meeting to make four stages of the planning activities, the implementation of actions, observations and reflections. 2) Observation is carried out by the principal as a collaborator supervisor, ending with reflection to see the positive and negative aspects as a basis for planning the next action in cycle 2. With clinical supervision, there is an increase in teacher competence at the beginning of activities 71.43% to 93.73% an increase of 22.30%.